Microscopic monitoring provides information on structure and properties during biocatalyst immobilization - Bidmanova, Sarka; Hrdlickova, Eva; Jaros, Josef; Ilkovics, Ladislav; Hampl, Ales; Damborsky, Jiri; Prokop, Zbynek (Biotechnology journal, 2014)
Enzymes have a wide range of applications in different industries owing to their high specificity and efficiency. Immobilization is often used to improve biocatalyst properties, operational stability, and reusability. However, changes in the structure of biocatalysts during immobilization and under process conditions are still largely uncertain. Here, three microscopy techniques - bright-field, confocal and electron microscopy - were applied to determine the distribution and structure of an immobilized biocatalyst. Free enzyme (haloalkane dehalogenase), cross-linked enzyme aggregates (CLEAs) and CLEAs entrapped in polyvinyl alcohol lenses (lentikats) were used as model systems. Electron microscopy revealed that sonicated CLEAs underwent morphological changes that strongly correlated with increased catalytic activity compared to less structured, non-treated CLEAs. Confocal microscopy confirmed that loading of the biocatalyst was not the only factor affecting the catalytic activity of the lentikats. Confocal microscopy also showed a significant reduction in the pore size of lentikats exposed to 25% tetrahydrofuran and 50% dioxane. Narrow pores appeared to provide protection to CLEAs from the detrimental action of cosolvents, which significantly correlated with higher activity of CLEAs compared to free enzyme. The results showed that microscopy can provide valuable information about the structure and properties of a biocatalyst during immobilization and under process conditions.
Keywords: Animals; Helminth Proteins; Dioxanes; Furans; Structure-Activity Relationship; Schistosoma japonicum; dioxany; furany; biokatalýza; Hydrolases; vztahy mezi strukturou a aktivitou; proteiny červů; zvířata; Enzyme Stability; hydrolasy; mikroskopie; Biocatalysis; Microscopy; stabilita enzymů